Ceramic-on-metal bearing in short stem total hip arthroplasty: ions, functional and radiographic evaluation at mid-term follow-up. Issue 2 (December 2020) - Saracco, Michela; Maccauro, Giulio; Urbani, Andrea; Ciavardelli, Domenico; Persichilli, Silvia; Ancillai, Giulio; Pasqualetti, Patrizio; Calvisi, Vittorio; Logroscino, Giandomenico
Introduction: The aim of this study is to evaluate clinical, radiographic and laboratory results of ceramic-on-metal (CoM) (hybrid hard bearing) in total hip arthroplasty (THA), associated with a short stem implant. Methods: From a cohort of 37 patients suffering from primary or secondary hip osteoarthritis who underwent THA using CoM bearing, 19 were suitable for this study. All procedures were performed by the same surgeon using a posterior-lateral approach. All patients were compared clinically using the Harris Hip Score (HHS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), visual analogue scale (VAS), 12-item Short Form Health Survey (SF12F/M), and radiographically (offset, CD angle, limb length discrepancy, cup inclination and anteversion, subsidence, osseointegration, heterotopic ossification). Blood samples were collected in order to evaluate chromium (Cr) and cobalt (Co) ions level. Radiographic evaluations were carried out by 3 different blinded surgeons. A statistical analysis was performed. Results: At a mean follow-up of 97 (73–125) months all implanted stems were well-positioned and osseointegrated. Clear improvements were observed for clinical scores comparing preoperative and postoperative values. Radiographic evaluation showed a good ability to restore proper articular geometry. Cr ion analysis revealed values below the safety threshold except for 1 case. Serum levels of Co were below the threshold in all patients. There was a statistically significant correlation only between Cr metal ions and length of follow-up. Conclusions: CoM bearing has proven to be reliable and safe at a mean 8-year follow-up for patients in whom the components were correctly implanted. The rise of blood metal ions was minimal and involved neither systemic or local toxicity nor influenced clinical results.